Beyond SERVQUAL: Culturally Sensitive Approach for Optimizing School Service Quality Management - Nuryani, Lilis Kholisoh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study analyses how service quality management can be optimized in schools to improve customer experience, focusing on SERVQUAL dimensions, including cultural relevance. A qualitative approach with a case study type was chosen to answer the focus of the study, using interview, observation, and documentation methods. Data analysis was carried out in stages, starting with data reduction, data presentation, and conclusion. The study results indicate that the dimensions of tangibles (physical facilities), reliability, responsiveness, assurance, and empathy significantly affect customer satisfaction and trust. This study also found that cultural relevance is important in increasing student and parent engagement. Respect for their culture makes the educational experience more positive. This study provides important implications regarding the need for schools to manage all dimensions of service quality well, including understanding and accommodating student cultural diversity, to create a more inclusive and supportive learning environment. This study is expected to be a reference in developing better education policies.